Packaging With Different Color Bags Under Light Exposure Improves Baby Mustard (Brassica juncea var. gemmifera) Postharvest Preservation - Lin, Peixing; Di, Hongmei; Ma, Jie; Wang, Yating; Wei, Jia; Jian, Yue; Li, Zhiqing; Xu, Jingyi; Zheng, Yangxia; Li, Huanxiu; Zhang, Fen; Sun, Bo (Frontiers in Plant Science, 2022)
Effect of packaging baby mustard into bags of different color under light exposure on its visual quality and the content of chlorophyll, carotenoids, and glucosinolates at 20 °C was investigated. Packaging with seven color bags under light exposure prolonged the shelf life, especially green (GB), blue (BB), and transparent (TB) bags with holes, and their shelf life was 1.7, 1.6, and 1.6 times that of the control, respectively. The GB and BB treatments delayed the deterioration of the sensory quality in baby mustard during storage. The BB and TB treatments not only increased chlorophyll and carotenoids content in baby mustard during storage but also enhanced the accumulation of glucosinolates by inhibiting their degradation, especially the BB treatment. Overall, the results demonstrate that the BB treatment is a promising technique for maintaining the postharvest quality of baby mustard.